What is the relationship between exposure to environmental pollutants and severe mental disorders? A systematic review on shared biological pathways - Pierluigi Catapano; Mario Luciano; Salvatore Cipolla; Daniela D'Amico; Alessandra Cirino; Maria Chiara Della Corte; Gaia Sampogna; Andrea Fiorillo (Brain, Behavior, & Immunity - Health)
Severe mental disorders are multi-dimensional constructs, resulting from the interaction of genetic, biological, psychosocial, and environmental factors. Among the latter, pollution and climate change are frequently being considered in the etiopathogenesis of severe mental disorders. This systematic review aims to investigate the biological mechanisms behind the relationship between environmental pollutants, climate change, and mental disorders. An extensive literature search was performed on PubMed, Scopus, and APA PsycInfo databases according to the PRISMA guidelines. Articles were considered eligible if they involved humans or animals examining the association between exposure to environmental pollutants and if the resulting biological mechanisms that may have an impact on mental health and may support or even cause severe mental disorders (SMD) are assessed. For this reason, only studies dealing with biomarkers or biological pathways were taken into account. The 47 papers included in the review were divided into two groups: those conducted on human participants (15 studies) and those utilizing animal models (31 studies); one study included both humans and animals. Studies carried out with humans, which are mainly focused on measuring the impact of particulate matter (PM2.5 and PM10) exposure on mental health, showed an increased risk of depression or psychotic relapses through the inflammation and oxidative stress pathways, or through the alteration of the hypothalamic-pituitary-adrenal (HPA) axis. Animal models showed the potential impact of pollution on brain functioning through increased inflammatory responses, oxidative stress, HPA axis disruption, hippocampal damage, and neurotransmitters dysregulation. Our findings show that environmental pollutants have an impact on human mental health through different biological pathways. The biological mechanisms by which environmental pollution and climate change influence the onset and exacerbation of severe mental disorders are complex and include gene expression, inflammation, oxidative stress, and anatomical brain changes. A better understanding of those pathways is important for the progress of knowledge on the pathophysiology of severe mental disorders according to the one health model, that promotes a collaborative, multisectoral, and transdisciplinary approach across various levels to optimize health outcomes by recognizing the interconnectedness of humans, animals, plants, and their shared environment.